2015
DOI: 10.1021/jo502642n
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Catalyzed Double-Decarboxylative Cross-Coupling of α-Keto Acids with Cinnamic Acids in Water: A Strategy for the Preparation of Chalcones

Abstract: A silver-catalyzed double-decarboxylative protocol has been proposed for the construction of chalcone derivatives via cascade coupling of substituted α-keto acids with cinnamic acids under the mild aqueous conditions. The developed method for constructing C-C bonds via double-decarboxylative reactions is efficient, practical, and environmentally benign by using the readily available starting materials. It should provide a promising synthesis candidate for the formation of diverse and useful chalcone derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 72 publications
0
38
0
Order By: Relevance
“…We speculated that it is formed through the oxidative cleavage of benzoxazoles followed by condensation with α-keto acids. And the control experiments 30 confirmed that the o-aminophenol might be the key intermediate. 9b Recently, Liu and Li et al have successfully achieved the decarboxylative 2-acylation of oxazoles and thiazoles with α-keto acids under a novel Co/Ag 2 CO 3 catalytic system (Scheme 3).…”
Section: Formation Of Csp 2 -Csp 2 Bondsmentioning
confidence: 77%
See 3 more Smart Citations
“…We speculated that it is formed through the oxidative cleavage of benzoxazoles followed by condensation with α-keto acids. And the control experiments 30 confirmed that the o-aminophenol might be the key intermediate. 9b Recently, Liu and Li et al have successfully achieved the decarboxylative 2-acylation of oxazoles and thiazoles with α-keto acids under a novel Co/Ag 2 CO 3 catalytic system (Scheme 3).…”
Section: Formation Of Csp 2 -Csp 2 Bondsmentioning
confidence: 77%
“…In this field, commercial avaliable Selectfluor has been widely utilized as 30 fluorine source to construct the C-F bond. 14 In 2014, we developed a novel Ag(I)-catalyzed decarboxylative acylfluorination of styrenes with α-keto acids and Selectfluor.…”
Section: Formation Of Csp 2 -X Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aryl radical is added to the cinnamate anion at the α -position, leading to the formation of chalcone with another molecular loss of carbon dioxide and Ag(I). 142 The strategy of using saturated propiophenones to produce unsaturated chalcones has also been demonstrated using a combination of decarboxylation and dehydrogenation (Scheme 8D). 147 The researchers crosscoupled aryl carboxylic acids using a PCy 3 -supported palladium catalyst to obtain chalcones in fair yields, which is an extension of the Heck reaction that overcomes the limits of its starting materials.…”
Section: Synthesismentioning
confidence: 99%